Alumina dissolution process to fabricate bimodal pore architecture alumina with superior green and sintered properties - Pandey V.; Panda S.K.; Singh V.K. (My University, 2025)
Herein, a straightforward, adaptable, and cost-effective approach has been proposed to realize the concept of dissolution of alumina in acidic aqueous media to fabricate porous alumina showing exceptional green machining properties and exhibiting good thermomechanical properties through in situ generated blowing agents and thermo-foaming process. The process involves dissolving alumina in concentrated sulfuric acid to generate aluminum hydroxide and aluminum sulfate, which act as blowing agents to produce pores in the final structure through a decomposition process at elevated temperatures. By varying the concentration of deionized water and acidification using sulfuric acid, different alumina slurries are prepared. Sintering shrinkage is well countered through simultaneous consolidation and decomposition process during the heat treatment, and a minimum shrinkage of 0.88% is achieved. In addition to its pore-forming properties, aluminum sulfate also provides strong binding effects to green bodies, contributing to their exceptional green machining properties. The resulting porous alumina exhibits a green flexural strength of up to 17 MPa, making it capable of bearing loads and forces during green machining. The sintered porous alumina fabricated in the study has a porosity range of 34.43%–59.24% and a flexural strength of 27.84–53.21 MPa. The prepared porous alumina also exhibits satisfactory thermal resistivity, with a minimum thermal conductivity of 1.23 W/m K, and has intra/intergranular space in the nano range. The coexistence of a combination of bimodal pores in a single monolithic matrix makes it exceptionally porous and suitable for an extensive spectrum of applications. © 2023 The American Ceramic Society.